Enzyme-linked immunosorbent assay (ELISAs) for metalloproteinase derived type II collagen neoepitope, CIIM—Increased serum CIIM in subjects with severe radiographic osteoarthritis - Bay-Jensen, Anne-Christine; Liu, Qi; Byrjalsen, Inger; Li, Yi; Wang, Jianxia; Pedersen, Christian; Leeming, Diana J.; Dam, Erik B.; Zheng, Qinlong; Qvist, Per; Karsdal, Morten A. (Clinical biochemistry, 2011)
In joint degenerative diseases, the collagens are degraded by matrix metalloproteinases and protein fragments are released to serum as potential biomarkers. A collagen type II specific neoepitope, CIIM, was identified (…RDGAAG 1053) by mass spectrometry. Two ELISAs against the neoepitope were developed. CIIM was measured in cartilage explants in the presence or absence of protease inhibitors. CIIM was measured in OA synovial fluid ( n = 51) and serum ( n = 156). Knee OA was graded by standard Kellgren–Lawrence (KL) score. The ELISAs showed good technical performance; CV%, < 13%. CIIM release from cartilage explants was blocked by the MMP inhibitor. CIIM was detected in synovial fluid. Furthermore, serum CIIM levels were significantly higher ( P < 0.05) in those individuals with mild or severe OA than in those with no OA. We developed a new biomarker for joint degenerative diseases, which we demonstrated was derived from MMP-degraded type II collagen.